The Influence of the Role of Driving Teachers and Principals’ Academic Supervision Management on the Success of the Project for Strengthening the Profile of Pancasila Students in Samarinda - Yuliana Yuliana; Yudo Dwiyono; Akhmad Akhmad (PT ARRUS Intelektual Indonesia, 2024)
The research objectives are: (1) To determine the influence of the role of driving teachers on the success of the Project for Strengthening the Profile of Pancasila Students in Samarinda, (2) To determine the influence of the principal's academic supervision management on the success of the Project for Strengthening the Profile of Pancasila Students in Samarinda, (3) To determine the influence the role of driving teachers and academic supervision management together in the success of the Strengthening Pancasila Student Profile Project in Samarinda. The method used is a survey with a quantitative approach that is causal (cause and effect). The total population was 133 people with a sample of 100 people. The data collection technique uses a rating scale which has been tested for validity and reliability. Data analysis techniques use descriptive and inferential statistics with simple linear regression formulas and multiple linear regression. The research results show that: (1) The role of the driving teacher influences the success of the Pancasila student profile by 51%. (2) The school principal's academic supervision management influences the success of the project to strengthen the profile of Pancasila students by 61.9%. 3) The role of the driving teacher and the principal's academic supervision management together influenced the success of the project to strengthen the profile of Pancasila students by 65.4%. This means that the more the role of teacher motivators and principals' academic supervision management increases, the greater the success of the project to strengthen the profile of Pancasila students.